Semantic Web Services for Web Databases - Ouzzani, Mourad; Bouguettaya, Athman; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Semantic Web Services for Web Databases introduces an end-to-end framework for querying Web databases using novel Web service querying techniques. This includes a detailed framework for the query infrastructure for Web databases and services. Case studies are covered in the last section of this book. Semantic Web Services For Web Databases is designed for practitioners and researchers focused on service-oriented computing and Web databases.
Introduction -- Ontological Organization of Web Databases -- Web Services Query Model -- Web Services Query Execution and Optimization -- Implementation and Experiments -- Current Advances in Semantic Web Services and Web Databases -- Conclusions, Open Issues, and Future Directions.
Keywords: Computer science; Computer Communication Networks; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Database Management; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computer Communication Networks